Analysis of Fluid Flow in Pipeline and Cyclone Systems for Preduster Coal Mill Indarung V Factory Using Flow Simulation - Akhmad Rais; Yolli Fernanda; Arwizet K; Andre Kurniawan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Cyclone is a tool for selling particulates from fluid streams without a filter. Cyclone in this case is to separate particulates from the air stream so they don't enter the coal mill. This study aims to analyze the effectiveness of the cyclone, pressure drop, and head loss in the system. The particles to be separated from the fluid stream are 9 microns in size. Pipe length for flow distribution is 67.24 m and 7 units of elbows. This analysis uses numerical methods with flow simulation features and compares them with theoretical results. Theoretical results obtained a pressure drop of 4042.74 Pa and a head loss of 607.82 m. This pressure drop is greater than the pressure fan, which is 1333 Pa. The simulation results of the inlet pipe 200 with a pressure drop of 4207.42 Pa, a head loss of 632.58 m, and an efficiency of 43%. At the inlet pipe 100 with a pressure drop of 4146.04 Pa, a head loss of 623.35 m, and an efficiency of 17%. At the inlet pipe 250 with a pressure drop of 4362.61 Pa, a head loss of 655.82 m, and an efficiency of 39%. Best results on pipe inlet 200. Cyclone merupakan alat untuk memisahkan partikulat dari aliran fluida tanpa filter. Cyclone dalam hal ini untuk memisahkan partikulat dari aliran udara supaya tidak masuk ke coal mill. Penelitian ini bertujuan untuk menganalisis efektivitas cyclone, pressure drop, dan head loss pada sistem. Partikel yang akan dipisahkan dari aliran fluida berukuran 9 mikron. Panjang pipa untuk distribusi aliran yaitu 67,24 m dan elbow sebanyak 7 unit. Analisis ini menggunakan metode numerik oleh fitur flow simulation dan membandingkannya dengan hasil teoritis. Hasil teoritis didapatkan pressure drop 4042,74 Pa dan head loss 607,82 m. Pressure drop ini lebih besar dari pressure fan yaitu 1333 Pa. Hasil simulasi inlet pipa 200 dengan pressure drop 4207,42 Pa, head loss 632,58 m, dan efisiensi 43%. Pada inlet pipa 100 dengan pressure drop 4146,04 Pa, head loss 623,35 m, dan efisiensi 17%. Pada inlet pipa 250 dengan pressure drop 4362,61 Pa, head loss 655,82 m, dan efisiensi 39%. Hasil terbaik pada inlet pipa 200.